"No safe haven": denying entry to the corrupt as a new anti-corruption policy. Issue 4 (5th October 2015) - Moiseienko, Anton
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to provide an overview of the "no safe haven" anti-corruption commitment recently announced by the G20. The essence of this approach lies in denying entry to individuals reasonably believed to be complicit in massive corruption. Design/methodology/approach – The paper is based on the analysis of international legal instruments and relevant domestic legislation (US statutes, in particular the Magnitsky Act 2012), as well as on scholarly discussions. Findings – Proceeding from the analysis of deficiencies in the current anti-money laundering regime, this paper makes an argument in favour of adoption of the "no safe haven" policy as a legal standard in anti-corruption cooperation, rather than a voluntary initiative. Practical implications – The adoption by states of the approach advocated in this paper will strengthen, or so it is submitted, the international anti-corruption regime. Importantly, it will help curb impunity of those who are shielded from investigation and prosecution in their home countries. Originality/value – This paper considers basic legal and policy arguments that support the "no safe haven" anti-corruption policy. Due to the novelty of this approach and the dearth of academic literature on this topic, this may be a valuable contribution to the current anti-corruption discussions.